Development of Story-Based E-Modules to Improve Reading Interest And Learning Outcomes of Fifth Grade Elementary School Students - Akhmad Qomaru Zaman; Intan Fajrin Febrianti; Rarasaning Satianingsih (Journal La Edusci, 2026)
The interest in reading is one of the most important problems of elementary education and tends to affect the learning outcomes of students. The purpose of this study was to design an electronic module based on picture story to enhance reading interest and learning outcomes among the fifth grade elementary school students. The research utilized Research and Development model that was adapted to eight steps namely needs analysis, product design, initial development, expert validation, limited trial, revision, extensive trial, and final evaluation. The research was carried out at Tambaksawah Elementary School, Sidoarjo, using expert validators, small trial group, and 57 students in the general implementation phase. The data were collected using observation, interviews, expert validation sheets, reading interest questionnaires, pretest and posttest instruments and analyzed using qualitative descriptive and quantitative descriptive methods. The findings demonstrated that the module developed was very feasible with subject matter validation of 88 percent, media validation of 90 percent and language validation of 85 percent. The limited trial showed that the module was practical and received positive responses from students, although some students required initial guidance in using it, although some needed to be initially guided on the use of the module. The wider application demonstrated that the interest of students in reading grew by 61.0 percent to 85.1 percent. There was also an improvement in learning outcomes as indicated by the increase in average pretest score of 60.5 to the average posttest score of 85.0 with an average N Gain of 0.62 in moderate category.